Novel Wireless Monitoring for Water Discharge in Industry - Mohd Azimie, Ahmad; Airul Sharizli, Abdullah (2016)
Water is an important natural resource which needs constant quality monitoring for ensuring its safe use. Keeping industrial water discharges so that it is always within a standard determined for domestic usage is a crucial task. As the country is making its progress through industrialization, our water resources are prone to a threat of pollution especially from the industrial activities. It is a challenge in the enforcement aspect as it is impossible for the authorities to continuously monitor the location of water resources due to limitation especially in man power, facilities and cost of equipment. This often lead to a too late to be handled situation. Traditionally, the water quality detection has been carried out manually wherein the water samples are collected and taken to the laboratories for analysis. Since these methods fail to deliver real time data, we propose a water quality monitoring system based on wireless sensor network which helps in continuous and remote monitoring of the water quality data. The system architecture is based on hierarchical topology in which the monitoring scenario is divided into four general areas; each forming a cluster comprising of several wireless sensor nodes responsible for sensing, data collection & processing and communication.